2009
DOI: 10.1210/en.2009-0532
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21-Deficient Mice Demonstrate Impaired Adaptation to Ketosis

Abstract: Fibroblast growth factor 21 (FGF21) is a key metabolic regulator. Expressed primarily in liver and adipose tissue, FGF21 is induced via peroxisome proliferator-activated receptor (PPAR) pathways during states requiring increased fatty acid oxidation including fasting and consumption of a ketogenic diet. To test the hypothesis that FGF21 is a physiological regulator that plays a role in lipid oxidation, we generated mice with targeted disruption of the Fgf21 locus (FGF21 knockout). Mice lacking FGF21 had mild w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
268
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 321 publications
(306 citation statements)
references
References 27 publications
29
268
3
Order By: Relevance
“…Previous studies from our laboratory and others have demonstrated that modulation of FGF21 levels either via pharmacology or using molecular interventions lead to a phenotype similar to that seen with TR␤ agonist treatment i.e. a significant improvement in serum lipid profile (10,22), increased rates of lipolysis, and an increase in liver fatty acid metabolism (4,32). These findings suggest that stimulation of lipolysis and hepatic fatty acid oxidation via FGF21 induction using TR␤-specific agonists has significant therapeutic potential.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies from our laboratory and others have demonstrated that modulation of FGF21 levels either via pharmacology or using molecular interventions lead to a phenotype similar to that seen with TR␤ agonist treatment i.e. a significant improvement in serum lipid profile (10,22), increased rates of lipolysis, and an increase in liver fatty acid metabolism (4,32). These findings suggest that stimulation of lipolysis and hepatic fatty acid oxidation via FGF21 induction using TR␤-specific agonists has significant therapeutic potential.…”
Section: Discussionmentioning
confidence: 95%
“…In transgenic mice, overexpression of Fgf21 improves insulin sensitivity and lowers glucose concentration (45). However, Fgf21 global knockout did not show a diabetic phenotype, although mice displayed a defect in lipid metabolism upon ketogenic diet treatment (46). In diabetic and obese conditions, both Fgf21 mRNA and serum FGF21 levels are paradoxically elevated, indicative of development of peripheral FGF21 resistance in the context of obesity (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…In the fed state, where ketogenesis is normally suppressed by insulin, the Fgf21 tg mice have increased ketogenesis compared with control mice (6). The Fgf21 knockout mice display mild obesity, hepatic steatosis, and glucose intolerance as well as impaired ketogenesis in response to fasting (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a part of the fibroblast growth factor (FGF) family proteins have been described to be involved in the regulation of metabolic processes and function in an endocrine manner (2,3,4,5,6). These proteins include FGF19, 21, and 23 and are distinguished from the rest of the FGF proteins by lacking the heparin-binding domain, allowing them to diffuse away from their tissue of origin (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation